Relaxation Affirmation Technique Increases Self Efficacy of Patients with Nasopharingeal Cancer - Ah. Yusuf; Ira Suarilah; Pandu Rahmat (Universitas Airlangga, 2010)
Introduction: Patient with nasopharynx cancer may experience emotional distres. Emotional distres and anxiety may lead to decrease self-efficacy. Clients with a negative perception of the health or low self-efficacy would become apathetic and disability in soluns problem as compensation of getting that disease. The purpose of this study was the relaxation affirmations techniques in order to increase self-efficacy patient with nasopharynx cancer.Methods: This study used pra-experiment pre-post test design. Population was taken from patient with nasopharynx cancer of Ear Nose and Throat (ENT) Patient Departement Dr. Soetomo Hospital at Surabaya. Sample comprised of 19 respondents who selected based on inclusion criteria. Independent variable was the relaxation affirmations. Dependent variable was self efficacy of nasopharyngeal cancer patients. Data were collected using the observation sheet.Results: The results showed that there was a significant influence of relaxation affirmation in increased self-effi cacy patient with nasopharynx cancer, with p = 0.008.Conclusion: Based on that results, it can be concluded that relaxation affirmations help patients nasopharyngeal cancer in THT Patient Departement Dr. Soeotomo Hospital at Surabaya in improving self-efficacy so that they would have ability to accept reality and belief in health pattern for optimalizing quality of life. Relaxation affirmations techniques including diaphragma breathing and affirmation decrease sympatic nerve activity and increase positive firm belief in patient.